UMKM di Kawasan Danau Toba Khususnya Daerah Balige - Kathleen Vellina Sitorus; Mariana Simanjuntak (UNIVERSITAS SERAMBI MEKKAH, 2024)
This research aims to analyze the effectiveness of digital marketing strategies in increasing the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the Lake Toba area, especially the Balige area. The method used is a qualitative approach by conducting in-depth interviews and participatory observation of several MSMEs in Balige. This research found that the implementation of digital marketing, through social media, websites and e-commerce platforms, has a positive impact on increasing sales and brand awareness for MSMEs. The obstacles faced include limited digital knowledge, access to technology and internet infrastructure. However, with the right training and mentoring, MSMEs are able to utilize digital marketing to expand their market share and compete at local and national levels. This study suggests collaboration between the government, private sector and academics to provide sustainable training and improve digital infrastructure in the Lake Toba area to support the sustainability and development of MSMEs.